2011
DOI: 10.1007/s10557-011-6328-2
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Cohort Study of Gastrointestinal Complications and Vascular Diseases in Patients Taking Aspirin: Rationale and Design of the MAGIC Study

Abstract: The MAGIC study will yield important findings with regard to the prevalence and incidence of gastrointestinal complications and related risk factors for low-dose aspirin users. It may also report that use of anti-secretory agents such as proton pump inhibitors reduces the risk of such complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 46 publications
0
14
0
Order By: Relevance
“…The details of the study design were published elsewhere [11]. Described briefly, the study consisted of high-risk CV patients taking low-dose aspirin for cardioprotection that were consecutively recruited from 63 nationwide institutions between April 2007 and September 2009.…”
Section: Methodsmentioning
confidence: 99%
“…The details of the study design were published elsewhere [11]. Described briefly, the study consisted of high-risk CV patients taking low-dose aspirin for cardioprotection that were consecutively recruited from 63 nationwide institutions between April 2007 and September 2009.…”
Section: Methodsmentioning
confidence: 99%
“…A large number of elderly people with cardiovascular disease, cerebrovascular disease and chronic joint pain have been prescribed low-dose aspirin, antithrombotic drugs, NSAIDs and corticosteroids for primary or secondary prevention of cardiovascular disease, cerebrovascular disorders and arthralgia (18)(19)(20)(21)(22). In the present study, a univariate analysis focused on prescribed medications indicated that low-dose aspirin, antithrombotic drugs and corticosteroids are exacerbating factors for bleeding gastric and/or duodenal ulcers in elderly patients compared with nonelderly patients.…”
Section: Discussionmentioning
confidence: 67%
“…Several studies have identified the use of NSAIDs, including low-dose aspirin, as being a significant cause of gastroduodenal ulcers (12)(13)(14)(15)(16)(17)(18)(19). A large number of elderly people with cardiovascular disease, cerebrovascular disease and chronic joint pain have been prescribed low-dose aspirin, antithrombotic drugs, NSAIDs and corticosteroids for primary or secondary prevention of cardiovascular disease, cerebrovascular disorders and arthralgia (18)(19)(20)(21)(22).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this edition of Cardiovascular Drugs and Therapy, Origasa and colleagues describe the rationale and design of the MAGIC Study, a large Japanese cohort study designed to assess the frequency of gastrointestinal complications associated with low-dose aspirin therapy [1]. Bleeding, particularly from the gastrointestinal tract is the most important adverse effect of aspirin but its frequency and consequences have not been well studied.…”
mentioning
confidence: 99%